Pengaruh Terapi Stretching dan Akupressure terhadap Nyeri Sendi pada Lansia dengan Gout - Widyasih Sunaringtyas; Nian Afrian Nuari; Widhianti Widhianto (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2019)
Gout is a joint disease due to the high uric acid in the blood which can cause joint pain. The purpose of this study was to analyze the influence of stretching and acupressure combination therapy on joint pain in the elderly with gout. This research used Pre experiment research design with One group pre test post test without control method, the sample consists of 15 subjects selected by Purposive sampling technique. The variable measured in this study is the level of joint pain in elderly gout. The measuring instrument of this study used pain observation sheets. This study used the Wilcoxon Signed Ranks Test statistical test with significance (α = 0.05). The results showed that pain before intervention mostly experienced moderate-scale pain (4-6), while after intervention most experienced mild-scale joint pain (1-3), and there were effects of stretching and acupressure combination therapy on elderly joint pain with gout (p value = 0,000). This is because stretching and acupressure can improve fitness, facilitate the transportation of substances, accelerate blood circulation and increased levels of endorphins that can increase the level of health in the joints. Thus stretching and acupressure can be used as alternative therapies to reduce pain to improved the quality of life for the elderly.